Development of an Interactive Multimedia Based E-modul on Geometric Isomer Material - Zakaria, Andi; Enawaty, Eny; Lestari, Ira; Muharini, Rini; Erlina, Erlina (Universitas Pendidikan Mandalika, 2024)
Research and development of interactive multimedia based e-modules on geometric isomers material has the aim of determining the validity and response of students to interactive multimedia based e-modules on geometric isomers material. This e-module was developed to help students study geometric isomers material. This research uses the Research and Development (R&D) method with the ADDIE model. Validation techniques were analyzed using Content Validity Ratio (CVR) and Content Validity Index (CVI). Collecting data from student response questionnaires uses measurement techniques with indirect communication. The results of product validation from every aspect, both in e-modules and interactive videos, obtained a CVI value of 0.99 and were declared valid and suitable for use. The results of the student response questionnaire in the initial field test reached an average of 89.72% in the very good category and the main field test reached an average of 88.16% in the very good category.